2013
DOI: 10.5194/dwes-6-1-2013
|View full text |Cite
|
Sign up to set email alerts
|

Natural organic matter removal by ion exchange at different positions in the drinking water treatment lane

Abstract: Abstract. To guarantee a good water quality at the customers tap, natural organic matter (NOM) should be (partly) removed during drinking water treatment. The objective of this research was to improve the biological stability of the produced water by incorporating anion exchange (IEX) for NOM removal. Different placement positions of IEX in the treatment lane (IEX positioned before coagulation, before ozonation or after slow sand filtration) and two IEX configurations (MIEX ® and fluidized IEX (FIX)) were comp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 27 publications
2
17
0
Order By: Relevance
“…The SIX process provided only 10-20% removal of the highest MW (>20,000 Daltons) biopolymer fraction, comprising organic colloids, polysaccharides and protein like substances. This outcome is consistent with that from other studies which have reported low removal of the highest MW organics (biopolymers) by IEX (Mergen et al 2009;Huber et al 2011;Grefte et al 2013). This is a phenomenon related to decreasing charge density with increasing MW and/or size exclusion, where the organics are prevented from entering the IEX resin pores (Croué et al 1999;Humbert et al 2007).…”
Section: Resultssupporting
confidence: 92%
“…The SIX process provided only 10-20% removal of the highest MW (>20,000 Daltons) biopolymer fraction, comprising organic colloids, polysaccharides and protein like substances. This outcome is consistent with that from other studies which have reported low removal of the highest MW organics (biopolymers) by IEX (Mergen et al 2009;Huber et al 2011;Grefte et al 2013). This is a phenomenon related to decreasing charge density with increasing MW and/or size exclusion, where the organics are prevented from entering the IEX resin pores (Croué et al 1999;Humbert et al 2007).…”
Section: Resultssupporting
confidence: 92%
“…Thus IEX and coagulation are supplementary to each other (Bolto et al 2002). Nanofiltration is able to remove all NOM fractions (Matilainen et al 2004), but this process is more expensive and has a higher environmental impact (Liikanena et al 2006) than IEX (Grefte et al 2013). …”
Section: Discussionmentioning
confidence: 97%
“…The main group of natural organic matter (NOM) present in raw water sources are dissolved humic substances (HS) (Baalousha et al, 2008). Their presence in the water is quite troublesome for many reasons, e.g., they are responsible for water taste, smell and, most importantly, they act as precursors of disinfection by-products (Grefte et al, 2013;Krupińska et al, 2013;Rajca, 2015). Disinfection by-products are a product of the oxidation of organic compounds with the use of chlorine or ozone, leading to the formation of carcinogenic chlorine-derived organic compounds and non-fully oxidized organic compounds, respectively (Bond et al, 2014;Tubić et al, 2013).…”
Section: Introductionmentioning
confidence: 99%